Oscilacije nevtralnih mezonov - Bortolato, Blaž (Matrika, 2016)
A phenomenon of oscillations (mixing) of neutral mesons is presented. The phenomenon is described through Feynman's diagrams and quantitatively by solving Schrodinger's equation with effective Hamiltonian Operator. A phenomenon of mixing mesons Dsup0 is described in more detail as well as a process of determining a mixing parameter y. This is followed by results of measurements of Belle detector, the mentioned mixing parameter for mixing a system of mesons Dsup0.
Keywords: fizika osnovnih delcev; mešanje mezonov; mixing; neutral mesons; nevtralni mezoni; particle physics